The Effect of Active Range of Motion (ROM) Training on Muscle Strength of Non-Hemorrhagic Stroke Patients in BIDDOKKES Polda Metro Jaya - Millya Helen; Mila Evilianti; Ratna Juita (Nursing and Health Sciences Journal (NHSJ), 2021)
A stroke is a blood circulation disorder in the brain that causes disturbances in other body parts. Non-hemorrhagic stroke causes delays in movement due to muscle weakness. In Indonesia, the death rate due to stroke occupies the first position in Southeast Asia. WHO stated that 328,524 Indonesians died from a stroke. The high incidence of stroke makes researchers want to know the effect of giving active Range Of Motion (ROM) on muscle strength in non-hemorrhagic stroke patients at the Polda Metro Jaya Health Center. This study aims to determine the effect of active range of motion (ROM) exercise on muscle strength in non-hemorrhagic stroke patients at the Polda Metro Jaya Health Department in 2021.Research design is a quantitative analysis with a pre-experiment (one group's pre-post test) design. The sample in this study amounted to 17 respondents, and the determination of the sample using simple random sampling. The independent variable is Active Range Of Motion (ROM), and the dependent variable is muscle strength in patients with non-hemorrhagic stroke. This study used the Wilcoxon statistical test. The results showed an effect of giving ROM in non-hemorrhagic stroke patients. The results of the Wilcoxon test before and after ROM intervention in the upper extremity showed a p-value = 0.001. Wilcoxon test results before and after ROM intervention in the lower extremities showed a p-value = 0.002. This study concludes that there is an effect of giving active ROM on the muscle strength scale of the upper and lower extremities in non-hemorrhagic stroke patients at the Biddokkes Polda Metro Jaya. It is hoped that the patient's family can train ROM independently in family members who have had a stroke.